A Study on Factors Demotivating Non - major Students in Learning ESP at Nam Dinh Industrial college= Nghiên cứu những nhân tố gây nên sự mất hứng thú đối với sinh viên không chuyên trong việc học tiếng Anh chuyên ngành tại trường Cao đẳng Công - Trần, Thị Thanh Bình (2019)
This study is an attempt to investigate factors demotivating the non-major students in learning ESP at Nam Dinh Industrial College. The main purposes of the study are to find out the main demotivating factors affecting students‟ motivation in ESP lessons and to offer some solutions to help students overcome their demotivation. The study data were collected by means of questionnaire for students, informal interviews with both teachers and students.